Corrosion Behaviours of Carbon Steels Coated by Graphene Epoxy in Different Solutions - Suharyadi, Hafid; Kasturi; Handoko, Susilo; Hasan, Burhanudin; Pratama, Daniswara Hasta (International Journal of Integrated Engineering, 2025)
Corrosion of carbon steel pipelines is a significant challenge in industrial applications, particularly in acidic and saline environments. This study investigates the corrosion resistance of ASTM A53 Grade B carbon steel coated with a graphene-epoxy composite. A 2%-wt graphene-epoxy coating was applied to the substrates using the bath method. Corrosion performance was assessed through potentiodynamic polarization in CH₃COOH 0.1 M, H₂SO₄ 0.1 M, HCl 0.1 M, and NaCl 3.5% solutions at room temperature. Scanning Electron Microscopy (SEM) analysis provided insights into coating thickness and elemental distribution. Results indicate significant improvements in corrosion resistance, with inhibition efficiencies exceeding 97% in HCl and H₂SO₄ solutions. A notable reduction in corrosion rate and current density was observed across all coated samples, with the graphene-epoxy layer forming a robust barrier against aggressive ions. SEM analysis revealed uniform graphene dispersion within the epoxy matrix and a consistent coating thickness of ±149.9 µm, supporting the enhanced corrosion resistance. However, the coatings exhibited reduced efficacy in CH₃COOH, attributed to potential degradation of the epoxy matrix in organic acid conditions. These results demonstrate the potential of graphene-epoxy coatings as potent anticorrosion agents for a variety of industrial applications, especially those that are acidic and chloride-rich. Future research should focus on optimizing formulations for organic acids to expand the applicability of this technology.